Effect of Problem-Based Learning on Students’ Academic Achievement in Digital Electronics in Ken Saro-Wiwa Polytechnic, Bori, Rivers State, South-South, Nigeria - Tugwell, Owo Offia (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
The study investigated the effect of Problem-Based Learning (PBL) on Students’ Academic Achievement in Digital Electronics in Ken Saro-Wiwa Polytechnic, Bori, Rivers State, South-South, Nigeria. Quasi-experimental pre-test post-test control design was used in the study. The sample of the study comprised 84 Higher National Diploma (HND) final year students of electrical and electronic engineering (Telecommunications and electronics option). Three research questions and one hypothesis were formulated and tested at 0.05 level of significance guided the study. The instrument used for data collection was a 20-item Digital Electronics Achievement Test Questionnaire (DEATQ) designed by the researcher and validated by two experts in electrical and electronic engineering from Federal Polytechnic, Nekede, Owerri, Imo State. Kuder-Richardson formula was used to obtain the instrument’s reliability coefficient as 0.87. Mean and t-test were used to answer the research questions and test the hypothesis at 0.05 level of significance. The findings of the study revealed among others that problem-based learning enhances students’ academic achievement in Digital Electronics. Consequently, it was recommended among others that engineering technology lecturers in Nigerian polytechnics and universities should use more of PBL and other student-centred teaching strategies in instructional delivery in order to boost students’ achievement in technology-based courses.